PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP PERFORMA PERANGKAT DESA DI KECAMATAN KELUMBAYAN BARAT KABUPATEN TANGGAMUS - Abdul Wahid Hasbullah (Jurnal Enterpreneur dan Bisnis (JEBI), 2024)
The reason for this study was to decide the impact of Organizational Culture and Work Motivation on the Performance of Regional Apparatus at the Village Apparatus, Kelumbayan Barat District, Tanggamus Regency. The populace taken in the review added up to 30 Village Apparatus. The example utilized was 30 individuals as indicated by the populace. In view of the consequences of the review, it was reasoned that the impact of Organizational Culture and Work Motivation on the Performance of Regional Apparatus at the Village Apparatus of West Kelumbayan District, Tanggamus Regency that there was an impact between authoritative culture (X1) and work inspiration (X2) together on the exhibition variable of town authorities in Kelumbayan District. West, somewhat there is an impact between hierarchical culture on the exhibition of town authorities in West Kelumbayan District and for work inspiration factors there is an impact between work inspiration on the presentation of town authorities. village officials in West Kelumbayan District